A model for innovation in higher education - Jakovljevic, M. (South African Journal of Higher Education, 2020)
An extensive research and awareness about the role of innovation at education exist, but insight is missing regarding an individual frame of innovation of how to empower an individual towards life-long innovation activities. There is no adequate model that provides a holistic approach to innovation in academic institutions. This paper explores multiple innovation issues culminating in the development of a model for innovation from an individual perspective. This paper argues that awareness and the dynamics of individual innovation is missing in academic environments. Academics’ engagements in innovation endeavours are scarce; there are visible symptoms of deeply embedded social, institutional, cultural and individual factors of innovation. This requires a holistic approach in innovation research. Awareness of an individual’s potential and his/her innovation development cycles, external and internal dynamics can contribute to multiple innovation sustainability. These are pillars of the ORED model (observation, revelation, exploration, design) and ever expanding cycles for innovation.